2020
DOI: 10.1186/s40463-020-00460-3
|View full text |Cite
|
Sign up to set email alerts
|

Anterior skull base reconstruction using nasoseptal flap: Cadaveric feasibility study and clinical implication [SevEN-001]

Abstract: Background Pedicled nasoseptal flap (PNSF) has significantly improved the surgical outcomes of endoscopic endonasal approach (EEAs) by reducing cerebrospinal fluid (CSF) leakage. The purpose of this study is to assess the feasibility of using a PNSF for anterior skull base (ASB) reconstruction and to describe a method to compensate for a short flap based on our results. Methods In this cadaveric study, ASB dissection without sphenoidotomy was performed using 10 formalin-fixed and 5 fresh adult cadaver specim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…25,28 In a similar light, some have questioned whether the distal aspect of the nasoseptal flap becomes randomly supplied, considering the flap length relative to the caliber of the posterior septal branch of the sphenopalatine artery. 29 The average nasoseptal flap length is around 6.0-7.0 cm, 30,31 and the mean posterior septal branch diameter is around 2 mm. 32 Considering the AEA flap is of similar length, and the AEA branches are ≤1 mm in diameter, 16,33 it is possible that the AEA flap could become random distally regardless of the possible axial blood supply.…”
Section: Discussionmentioning
confidence: 99%
“…25,28 In a similar light, some have questioned whether the distal aspect of the nasoseptal flap becomes randomly supplied, considering the flap length relative to the caliber of the posterior septal branch of the sphenopalatine artery. 29 The average nasoseptal flap length is around 6.0-7.0 cm, 30,31 and the mean posterior septal branch diameter is around 2 mm. 32 Considering the AEA flap is of similar length, and the AEA branches are ≤1 mm in diameter, 16,33 it is possible that the AEA flap could become random distally regardless of the possible axial blood supply.…”
Section: Discussionmentioning
confidence: 99%
“…Though the flap is very versatile with a robust arc of rotation and the ability to include a large mucosal surface, it has limited reach superiorly toward the posterior nasal wall of the frontal sinus, laterally toward the orbits, and inferiorly beyond the upper two thirds of the clivus [ 29 ] ( Figure 3 ). Cadaver studies have shown that total sphenoidotomy reduces the mean length of the nasoseptal flap by increasing the distance to the posterior wall of the frontal sinus [ 30 ]. Therefore, several modifications have been proposed to extend its reach.…”
Section: Indications Modifications and Postoperative Considerationsmentioning
confidence: 99%